2018
DOI: 10.3390/nu10111654
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid Content in Human Colostrum is Associated to Preterm/Full-Term Birth Condition

Abstract: Factors such as lactation stage and premature and small-for-gestational conditions could lead to great inter-individual variability in the carotenoid content of human milk. The aim was to analyze the carotenoid content in colostrum and mature milk of preterm (PT) and full-term (FT) mothers to establish whether they are significantly different and, if so, the stage of lactation when the differences are established. Samples of blood, colostrum, and mature milk were collected from Spanish donating mothers who gav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 63 publications
0
17
1
Order By: Relevance
“…According to other studies, the decrease occurs only between colostrum and mature milk and the mature milk then has a stable level of carotenoids [30,31,47]. This difference in carotenoid concentration between colostrum and mature milk suggests the occurrence of a special mechanism of transporting carotenoids into the mammary gland during the first day postpartum [30,41,46,48]. This may be associated with the importance of carotenoids, especially lutein, to the health and development of newborns from the first days of life, including decreasing oxidative stress, as well as protection of the retina and participation in its proper development [6,24,26].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…According to other studies, the decrease occurs only between colostrum and mature milk and the mature milk then has a stable level of carotenoids [30,31,47]. This difference in carotenoid concentration between colostrum and mature milk suggests the occurrence of a special mechanism of transporting carotenoids into the mammary gland during the first day postpartum [30,41,46,48]. This may be associated with the importance of carotenoids, especially lutein, to the health and development of newborns from the first days of life, including decreasing oxidative stress, as well as protection of the retina and participation in its proper development [6,24,26].…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies investigated the breastmilk carotenoid changes during lactation and found that their concentrations decreased with the duration of lactation [19,31,41,46]. Colostrum contains significantly higher concentrations of carotenoids compared to mature milk, regardless of dietary intake or plasma carotenoid concentration [19,30,31,41,46,47]. However, in our study, we did not find any differences in carotenoid concentration between the first and sixth month of lactation which may be explained by the fact that we analysed only mature milk.…”
Section: Discussionmentioning
confidence: 99%
“…The macular and brain carotenoid levels in infants following delivery are a result of infant intake from the colostrum and mother's milk, or infant formula; the characteristic yellow color of colostrum is due to the carotenoids present [236][237][238]. A recent study found that the colostrum of mothers that gave birth to premature infants contained lower concentrations of carotenoids as compared to mothers of full-term infants; however, lutein levels were not different, which authors speculate could be related to the significant role of lutein in development of the infant retina and brain [239]. Several studies have analyzed the carotenoid content in human breast milk across diverse populations worldwide [237,[240][241][242][243][244][245][246][247][248][249][250].…”
Section: Carotenoidsmentioning
confidence: 98%
“…In many respects, there is strong potential in neurocognitive function along with a healthy lifestyle to promote brain health ( Lindbergh et al., 2017 ). It is relevant to comment that the carotenoid content in breast milk is associated with pre-mature or non-mature birth condition, but this condition does not impair the content of lutein and xanthophylls that are directly related to the development of the retina and the baby's brain ( Xavier et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%